Pengaruh Struktur Modal, Return On Invested Capital, Aktiva Tetap, Dan Nopat Terhadap Economic Value Added Pada PT Prima Sentosa Lestari - Elidawati; Diana, Tio; Sumarson Goh, Thomas; Sagala, Edison (STIEM BONGAYA, 2023)
In running a company's business, every management in the company definitely needs to evaluate every performance carried out in the company's activities. Performance evaluation is carried out as a form of assessment to determine the company's ability to generate profits from its total assets. To be able to add to the economic value created by a company from its sales activities or strategy, an accurate problem solving is needed. One indicator of the value added of the investment made by the company is the Economic Value Added (EVA). This study uses descriptive methods and multiple linear regression analysis techniques. Descriptive method is a method of analyzing problems by collecting data and grouping them in order to describe each process, as well as the behavior of the object under study at PT Prima Sentosa Lestari. Primary data were collected and obtained through interviews and observations while secondary data were obtained from literature related to the research topic. The balance sheet, statement of changes in equity, cash flow statement and income statement taken from 2016-2020 are used as research objects. The results showed that Capital Structure had no effect on Economic Value Added at PT Prima Sentosa Lestari in 2016-2020, Return On Invested Capital had an effect on Economic Value Added at PT Prima Sentosa Lestari in 2016-2020, Fixed Assets had an effect on Economic Value Added at PT Prima Sentosa Lestari in 2016-2020, NOPAT affects Economic Value Added at PT Prima Sentosa Lestari in 2016-2020 and Capital Structure, Return On Invested Capital, Fixed Assets and NOPAT affects Economic Value Added at PT Prima Sentosa Lestari in 2016-2020